Lipomatosis of the Ileocaecal Valve: A Case Report - Hasan, Mizanul; Rahman, Meher Angez; Alshantti, Khalil (International Journal of Scientific Research and Management (IJSRM), 2024)
The lipomatosis of ileocecal valve is characterized by a diffuse infiltration of fatty tissue, most often in the submucous layer. The ileocecal valve becomes enlarged. Lack of distinct capsule differentiate the fat in this condition from a true lipoma. As lipomatosis of the ileocecal valve is a rare condition, with doubtful pathogenesis and somewhat controversial therapy the case is reported. It must be recognized and differentiated from true tumours.